THE LION AND THE DRAGON Britain and China: A History of Conflict - James, Lawrence (Weidenfeld & Nicolson, 2023)
THE LION AND THE DRAGON reveals the part that Britain played in the awakening of China, then covers relations between the two countries during the period when an aroused China did indeed shake the world. Lawrence James also follows the parallel trajectories of four competitive empires - the British, the Chinese, the Russian and the Japanese - during the nineteenth and twentieth centuries, and then the fortunes of a fifth imperial power, the United States. Successive British governments saw China as a source of wealth which needed to be protected. Local objections were seen off by force (the 'Opium' wars of 1839-42, 1856-7 and 1859-60) whose results proved that the Qing emperors could not protect their country. Indian troops were deployed in each campaign and manned Britain's small garrisons in Hong Kong, Shanghai and other Treaty ports. Yet Britain never sought to make China into another India. Rather it allowed the emperors and their officials to govern, so long as they were docile and amenable to British needs. Paramount were the internal stability and fiscal responsibility that were the lubricants of trade.